2006
DOI: 10.1002/bit.21021
|View full text |Cite
|
Sign up to set email alerts
|

Reactive azo dye reduction byShewanella strain J18 143

Abstract: A bacterial isolate designated strain J18 143, originally isolated from soil contaminated with textile wastewater, was shown to reduce intensely coloured solutions of the reactive azo dye, Remazol Black B to colourless solutions. Phylogenetic placement based on 16S rRNA gene sequence homology identified the bacterium as a Shewanella species. Based on results from analyses of the end products of dye decoloration of Remazol Black B and the simpler molecule, Acid Orange 7, using capillary electrophoresis, UV-visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 116 publications
(62 citation statements)
references
References 33 publications
4
58
0
Order By: Relevance
“…Here the reduction rate of the Fe(III) oxide was increased by a factor of 18, to approximately 0.2 mmol min Ϫ1 g protein Ϫ1 , in the presence of 10 M of the electron shuttles. All three flavins were equally effective as electron shuttles and gave similar results to those with AQDS, the "benchmark" exogenous electron shuttle used in many other studies to accelerate microbial Fe(III) and azo dye reduction (11,22). In addition, the rates of reduction of soluble Fe(III)-citrate were identical for both fumarate-and Fe(III)-citrate-grown cells, regardless of the addition of an electron shuttle, showing that although biological flavins and AQDS enhance the rate of reduction of insoluble Fe(III) oxides, they are not required for maximal rates of reduction of soluble, highly bioavailable Fe(III)-citrate that can diffuse into the cell and potentially cross the outer membrane to penetrate the periplasm.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…Here the reduction rate of the Fe(III) oxide was increased by a factor of 18, to approximately 0.2 mmol min Ϫ1 g protein Ϫ1 , in the presence of 10 M of the electron shuttles. All three flavins were equally effective as electron shuttles and gave similar results to those with AQDS, the "benchmark" exogenous electron shuttle used in many other studies to accelerate microbial Fe(III) and azo dye reduction (11,22). In addition, the rates of reduction of soluble Fe(III)-citrate were identical for both fumarate-and Fe(III)-citrate-grown cells, regardless of the addition of an electron shuttle, showing that although biological flavins and AQDS enhance the rate of reduction of insoluble Fe(III) oxides, they are not required for maximal rates of reduction of soluble, highly bioavailable Fe(III)-citrate that can diffuse into the cell and potentially cross the outer membrane to penetrate the periplasm.…”
Section: Resultsmentioning
confidence: 64%
“…The supernatants of Shewanella strain Hac334 cultures were fractionated using reversed-phase HPLC and screened for the presence of a redox mediator by testing for enhanced rates of decoloration of the azo dye Direct Blue 53 by the organism. In addition to promoting the reduction of insoluble metals, azo dye reduction by Shewanella species is also enhanced by the addition of electron shuttling compounds (22), making enhanced reduction and decoloration of azo dyes a suitable rapid screen for the presence of secreted redox mediators. The rate of decoloration by Shewanella cells was enhanced most by addition of the fraction eluted by 35% methanol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some azo dyes also are degraded under aerobic conditions (Sarayu & Sandhya, 2010;Ayed et al, 2011). However, the efficiency of the process may decrease in the presence of oxygen (Pearce et al, 2006), due to competition between oxygen and the dyes as electron acceptors. Although a concomitant increase in microbial biomass has been shown to occur in dye polluted water under aerobic conditions, the degradation process does not appear to Complete decolorization in 4 h.…”
Section: Biodegradation Via Reduction Processmentioning
confidence: 99%
“…Riboflavin (RF), flavin mononucleotide (FMN), and flavin-adenine dinucleotide (FAD) were identified as the dominant electron shuttles secreted by a diversity of Shewanella cells and shown to mediate extracellular reduction of insoluble Fe(III) minerals and organic molecules, including azo dyes (23,40). Field and Brady tested riboflavin and found that its presence during anaerobic reduction of azo dyes improves the overall kinetics of the reduction process (9).…”
mentioning
confidence: 99%